The Influence of Librarians' Attitudes on Users' Interest in Visiting Visitors at the Technical Implementation Unit (UPT) of the UIN Datokarama Palu Library - Timbang, Sahrul Sidiq; Iskandar, Iskandar; Dakhalan, Andi Muhammad (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study aims to examine the influence of librarians' attitudes on visitors' interest in using the UPT Library of UIN Datokarama Palu. The research employed a quantitative correlational design. The population consisted of students who used the UPT Library at UIN Datokarama Palu. Data were collected through questionnaires distributed to 81 respondents via Google Forms and analyzed using SPSS version 25. The findings reveal that librarians' attitudes significantly influence visitors' interest. The correlation between librarians' attitudes and visitors' interest was weak (5.7%) but positive, indicating that the stronger librarians' attitudes, the higher visitors' interest. Hypothesis testing showed that the t-value (2.191) exceeded the t-table value (1.990), leading to the rejection of H0 and acceptance of H1. This confirms a significant effect of librarians' attitudes on visitors' interest. The implications of this study suggest that librarians should foster positive and friendly attitudes when providing services and implement user education programs to help visitors optimize library resources.AbstrakPenelitian ini bertujuan untuk menguji pengaruh sikap pustakawan terhadap minat kunjung pemustaka di UPT Perpustakaan UIN Datokarama Palu. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian adalah mahasiswa yang menjadi pemustaka UPT Perpustakaan UIN Datokarama Palu. Data dikumpulkan melalui kuesioner yang disebarkan kepada 81 responden menggunakan Google Form dan dianalisis dengan bantuan SPSS versi 25. Hasil penelitian menunjukkan bahwa sikap pustakawan berpengaruh signifikan terhadap minat kunjung pemustaka. Nilai korelasi antara sikap pustakawan dan minat kunjung pemustaka tergolong lemah (5,7%) tetapi positif, yang berarti semakin baik sikap pustakawan, maka semakin tinggi pula minat kunjung pemustaka. Uji hipotesis memperlihatkan bahwa thitung (2,191) lebih besar dari ttabel (1,990), sehingga H0 ditolak dan H1 diterima. Temuan ini menegaskan adanya pengaruh signifikan sikap pustakawan terhadap minat kunjung pemustaka. Implikasi penelitian ini adalah pentingnya pustakawan untuk mengembangkan sikap positif dan ramah dalam pelayanan serta melaksanakan program pendidikan pemakai guna membantu pemustaka memanfaatkan layanan perpustakaan secara optimal.